Specification-based automated gui testing - Panayi, Charis; Sofokleous, Anastasis A.; Andreou, Andreas S. (My University, 2011)
GUI testing is currently one of the most expensive and time consuming processes in the software life-cycle and according to some estimates this cost can reach up to 50 to 70% of the whole cost of the project. This paper proposes a framework for specification-based automated GUI testing which employs a GUI analyzer for dynamic analysis and extraction of GUI object information, a system for automatic test case generation driven by Spec#, a test-case execution algorithm that executes test-cases automatically and a verifier that compares the expected with the actual result of the test. Preliminary experimental results demonstrate the efficiency and effectiveness of the framework.
Keywords: Automatic testcase generation; GUI testing; Object information; Software life cycles; Specification based testing; Test case; Test case generation; Graphical user interfaces; Information systems; Specifications; Cost benefit analysis